A Tutte polynomial for maps II: The non-orientable case. (May 2020) - Goodall, Andrew; Litjens, Bart; Regts, Guus; Vena, Lluís
Abstract: We construct a new polynomial invariant of maps (graphs embedded in a closed surface, orientable or non-orientable), which contains as specializations the Krushkal polynomial, the Bollobás—Riordan polynomial, the Las Vergnas polynomial, and their extensions to non-orientable surfaces, and hence in particular the Tutte polynomial. Other evaluations include the number of local flows and local tensions taking non-identity values in a given finite group.